EFFECTIVE WAYS TO IMPROVE ENGLISH LISTENING SKILLS - Baxriddinova Nasiba Abdumajidovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores effective ways to improve English listening skills, emphasizing practical strategies that can be applied by learners at different proficiency levels. Listening is a fundamental component of language acquisition, as it directly influences speaking, pronunciation, and overall communication ability. The study highlights the importance of consistent exposure to authentic audio materials such as podcasts, movies, and conversations with native speakers. It also examines techniques like active listening, note-taking, shadowing, and the use of subtitles to enhance comprehension. Furthermore, the article discusses the role of digital tools and language learning platforms in developing listening skills in a modern, technology-driven environment. Special attention is given to overcoming common challenges such as fast speech, unfamiliar accents, and limited vocabulary. By implementing these strategies, learners can significantly improve their listening comprehension and become more confident in real-life communication.